Field notes contributed by Lee A. Schoenewe, summer 2000 - Schoenewe, Lee A.et al (2000)
Summer report of birds found in northwest Iowa contributed by Lee A. Schoenewe. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of summer 2000. Epson - sheet feed